Comparative Legal Analysis of Educational Measures for Minors Who Have Committed an Administrative Offense in Kazakhstan and Ukraine - KOZYBAEVA, Gulmira B.; PIDDUBNYI, Oleksii Yu.; BALYKIN, Ivan I.; BALYKINA-HALANETS, Liudmyla I.; SHATKOVSKYI, Yaroslav N. (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019DO - 10.14505//jarle.v10.1(39).28, 2019)
Violation of law and order by adolescents has always been one of the urgent problems in the development of each state, which is faced not only by law enforcement agencies, but also by society as a whole, because the younger generation is the future of the country. The main purpose of the article is a complex legal characteristic of educational measures against minors who have committed an administrative offense in Kazakhstan and Ukraine, and their comparative characteristics. The purpose of the article stipulated the use of analytical and comparative analysis as the main methods. The main scientific approach when considering this issue is that in the system of measures of administrative and legal coercion it is necessary to single out educational measures that are unlawfully identified with administrative penalties. Based on the results of the analysis, a number of legislative recommendations have been offered regarding the improvement of individual rules governing this issue. In the future, it will be of interest to analyze the effectiveness of existing norms of administrative educational influence on minors through the study of statistical data on the level of offenses committed and measures applied which by its volume goes beyond the scope of this work and is the subject of a separate research.